Motivations to prepare after the 2013 Cook Strait Earthquake, N.Z. (October 2018) - Doyle, Emma E.H.; McClure, John; Potter, Sally H.; Becker, Julia S.; Johnston, David M.; Lindell, Michael K.; Johal, Sarbjit; Fraser, Stuart A.; Coomer, Maureen A.
Abstract: We investigated responses to the 2013 Cook Strait earthquake sequence, New Zealand. This included two foreshocks (M5.7 and M5.8) and a mainshock doublet pair: M6.5 Cook Strait (CS) earthquake on 21st July and M6.6 Lake Grassmere (LG) earthquake on Friday 16th August. We examined relationships between preparedness, experience and beliefs during the earthquakes, as well as concern and subsequent preparedness actions. Results indicate that earthquake characteristics (e.g., time, location) influence the types of preparedness actions. While there was a reduction in new actions from the first mainshock doublet earthquake (CS) to the second (LG), there were a large number of participants who reviewed or revisited their prior actions, related to their beliefs about impacts, in a form of problem-focused targeted action. Females took more actions than did males, and had a higher rate of immediate aftershock concern. For all participants, concern was greater after the CS earthquake than after the full earthquake sequence, supporting the findings of McClure et al. (2016) that there is a limited window after an event to maximise the opportunity for effective preparedness initiatives. Findings additionally suggest that such post-earthquake preparedness initiatives should consider the impacts that elicited the highest rate of concern in an event, and should tailor messages towards them. While this earthquake sequence resulted in low levels of impact and damage, it presents interesting findings regarding how disruption (in lieu of major damage) influences earthquake preparedness actions, which is particularly important to understand in highly active regions often exposed to smaller impact events. Highlights: Self-reported preparedness actions and concern after an earthquake sequence. Earthquake characteristics (e.g. time of day) affect actions (e.g. due to being at work). Actions relate to greatest belief of potential event impact. Participants displayed problem-focused targeted action depending on impact beliefs. Concern decreased after all earthquakes than after the first large earthquake.